(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
The importance of blended learning in teaching foreign languages is addressed and provides viewpoints on the importance of blended learning in enhancing students` knowledge, skills and competencies in language learning in the modern learning process. Today, much attention is paid to a radical change in the way English is taught. Students are becoming more involved in learning foreign languages through online learning with a teacher in collaboration and developing language skills.